2014
DOI: 10.1111/1755-0998.12306
|View full text |Cite
|
Sign up to set email alerts
|

Targeted detection of mammalian species using carrion fly‐derived DNA

Abstract: DNA analysis from carrion flies (iDNA analysis) has recently been promoted as a powerful tool for cost- and time-efficient monitoring of wildlife. While originally applied to identify any mammalian species present in an area, it should also allow for targeted detection of species and individuals. Using carrion flies captured in the Taï National Park, Côte d'Ivoire, we assessed this possibility by (i) screening carrion fly DNA extracts with nonspecific and species-specific PCR systems, respectively, targeting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 35 publications
0
59
0
Order By: Relevance
“…Invertebrate-derived DNA (iDNA) is an offshoot of this approach that involves the extraction of genetic material of animals via the flesh-eating or haematophagous invertebrates that parasitise them (Schnell et al, 2015;Schubert et al, 2015;Lee et al, 2016). To date, most iDNA studies have focused on terrestrial vertebrates and have extracted host DNA from insects, ticks, or leeches.…”
Section: Introductionmentioning
confidence: 99%
“…Invertebrate-derived DNA (iDNA) is an offshoot of this approach that involves the extraction of genetic material of animals via the flesh-eating or haematophagous invertebrates that parasitise them (Schnell et al, 2015;Schubert et al, 2015;Lee et al, 2016). To date, most iDNA studies have focused on terrestrial vertebrates and have extracted host DNA from insects, ticks, or leeches.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of mechanically transmitted viruses by flies are the transmission of turkey coronavirus and rotavirus by domestic houseflies ( Musca domestica ) [57,58]. Furthermore, carrion flies have been used for the targeted detection of mammalian species DNA and biodiversity [59,60]. Since carrion flies feed on many vertebrate carcasses, it is feasible to use them for the detection of viruses from deceased animals.…”
Section: Mosquitoes As “Flying Syringes” For Virus Surveillancementioning
confidence: 99%
“…This combines VEM with invertebrate-derived DNA (iDNA), a term designating the genetic material ingested by invertebrates feeding on vertebrates [77]. Several studies have shown that iDNA from a variety of vertebrate species can be identified from field-caught animals, including mosquitoes [78,79], carrion flies [59,60,80], biting midges [81], leeches [71,82] and ticks [83]. For the identification of host DNA from arthropod blood meals, PCR-based or serological techniques are traditionally used [84,85,86,87,88].…”
Section: Combining Vem With Idnamentioning
confidence: 99%
“…The Ta€ ı sample set offered a good opportunity to assess the extent of this underestimation/the sensitivity of the first assay. As Ta€ ı chimpanzees predominantly hunt colobine monkeys (95% of their prey; [Boesch, 1994;Boesch and Boesch-Achermann, 2000], we tested this sample set with a specific colobine assay targeting a 122 bp fragment of the mitochondrial 12S ribosomal RNA gene (12S); this assay was shown to amplify DNA from all colobine species occurring in Ta€ ı [Schubert et al, 2014]. All samples that were positive with this assay were then also tested using another specific colobine assay targeting an approximately 480 bp fragment of the mitochondrial control region (CR; [Minhos et al, 2013]) and rarely used in our laboratory, in order to further control for the possibility of contamination by PCR products.…”
Section: Molecular Analysismentioning
confidence: 99%